The Development of Puzzle Board Card Media to Enhance Students' Critical Thinking Skills in Science Learning - Ziliwu, Siskawati; Anas, Nirwana (Jurnal Elementaria Edukasia, 2024)
Critical thinking ability is an essential skill possessed by elementary school students in the 21st century learning era. One tool that supports the development of this ability is puzzle card board media. This research aims to develop and test the effectiveness of this media in improving the critical thinking skills of fifth grade students in elementary schools. The research method applied is research and development (R&D) using the ADDIE research model which consists of the Analysis, Design, Development, Implementation and Evaluation stages. The product developed in this research is puzzle card board media which is adapted for science subjects, then its validity is tested by media experts and material experts, and distributed via questionnaires to teachers and class V students at SDIT Ummi Aida. The research subjects consisted of 29 class V students. The object of this research was the development of puzzle card board media. Based on the results of research and development, it was concluded that this puzzle card board media met the research criteria as evidenced by a media validation score of 93.7%, and a material validation score of 90.6% with a value range of 76%-100%, including in the very valid category. This research received responses from teachers with a score of 98.6% and responses from students with an average score of 86.7% in the practical or very good category for use. This shows that the puzzle card board media is included in the criteria of valid, practical and effective use as teaching material for teachers and students. The author recommends that this research is not only centered on improving critical thinking, but on developing creativity in accordance with 21st century learning skills